2019
DOI: 10.3390/cells8080941
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Lipids Are Not a Source of Arachidonic Acid for Lipid Mediator Signaling in Human Foamy Monocytes

Abstract: Human monocytes exposed to free arachidonic acid (AA), a secretory product of endothelial cells, acquire a foamy phenotype which is due to the accumulation of cytoplasmic lipid droplets with high AA content. Recruitment of foamy monocytes to the inflamed endothelium contributes to the development of atherosclerotic lesions. In this work, we investigated the potential role of AA stored in the neutral lipids of foamy monocytes to be cleaved by lipases and contribute to lipid mediator signaling. To this end, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 75 publications
2
14
0
2
Order By: Relevance
“…Yeast-derived zymosan has been used for years as a model to study PLA 2 -dependent pathways for lipid mediator production in murine macrophages [51][52][53][54][55]. Conversely, OpZ has been used most often to stimulate circulating cells such as monocytes and neutrophils [11,[56][57][58]. Zymosan activates PLA 2 via engagement of dectin-1 receptors [9,10], while heat-inactivated OpZ does it by engaging Fc receptors [11,12].…”
Section: Resultsmentioning
confidence: 99%
“…Yeast-derived zymosan has been used for years as a model to study PLA 2 -dependent pathways for lipid mediator production in murine macrophages [51][52][53][54][55]. Conversely, OpZ has been used most often to stimulate circulating cells such as monocytes and neutrophils [11,[56][57][58]. Zymosan activates PLA 2 via engagement of dectin-1 receptors [9,10], while heat-inactivated OpZ does it by engaging Fc receptors [11,12].…”
Section: Resultsmentioning
confidence: 99%
“…A striking feature of the present work is that, of all major fatty acids released by MT-III, AA was excluded from incorporating into neutral lipids. We have recently shown that human monocytes exposed to micromolar amounts of AA do incorporate the fatty acid into neutral lipids, implying that this pathway is fully functional in these cells [ 88 ]. This is an interesting concept because recent work has suggested a link between lipid droplets and AA metabolism in mast cells and neutrophils [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contradicting results have, however, arisen from the observation that free AA treatment is able to induce p38 and JNK signaling in human monocytes, as well as to generate a foam-like phenotype by promoting the accumulation of TG, CE and AA itself in LDs [131]. This pool is, however, not used for eicosanoid production [132], but still represents a mechanism that may favor the ATM phenotype distinctive of obesity as lipid-laden monocytes migrate into AT. JNK signaling is associated with apoptotic mechanisms and accordingly, AA treatment of RAW cells caused cell cycle arrest and apoptosis in a JNK-dependent manner [133].…”
Section: Ufamentioning
confidence: 99%